The Effectiveness Of The Baas Program (Father Following Stunting Children) In The Framework Of Reduce The Rate Of Stunting Incidents At Deagintungkerta, The Work Area Of Puskesmas Anggadita Klari District, Karawang District, In 2022 - Erlis Herliati; Nanik Yuliwati (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
Background : In order to support stunting reduction activities, the West Java BKKBN has formed a family assistance program which is carried out by a family assistance team consisting of midwives, cadres and PKK staff to eliminate the main factors causing stunting. Research purposes : To find out more in-depth information about the effectiveness of the BAAS (Foster Father of Stunting Children) program in the form of input, output and process indicators in order to reduce the incidence of stunting in Gintungkerta Village, Kari District, Karawang Regency in 2022. Types of research : The research was conducted in June 2023. The informants and key informants consisted of 16 people. This study uses in-depth interview techniques with a qualitative approach method. Research result : Input: